Analyzation of the Resistor-Inductor-Capacitor Circuit - Martin D. Elton (Undergraduate Journal of Mathematical Modeling: One + Two, 2017)
Starting with the basics of what a Resistor-Inductor-Capacitor circuit (RLC) is, i.e. its fundamental components, and ending with practical applications using advanced calculus to aid in predetermining the results and circuit design, this paper analyzes the RLC circuit via an advanced calculus based approach.